Guinea-Bissau Teachers : SABER Country Report 2012 - World Bank (Washington, DC, 2014)
In 2012, Guinea- Bissau joined the Russia Education Aid for Development (READ) trust fund program, the goal of which is to help countries improve their capacity to design, carry out, analyze, and use assessments for improved student learning. As part of the READ trust fund program, and in order to gain a better understanding of the strengths and weaknesses of its existing assessment system, Mozambique participated in a formal exercise to benchmark this system under The World Bank's Systems Approach for Better Education Results (SABER) program. SABER is an evidence-based program to help countries systematically examine and strengthen the performance of different aspects of their education systems. SABER-teachers are a component of the SABER program that focuses specifically on benchmarking teacher policies and systems. The goal of SABER-teachers is to attract, retain, develop, and motivate great teachers. Teachers system tends to be comprised of seven main types of activities, each of which serves a different purpose and addresses different information needs. These three main types are: teacher expectations, preparing, skill matching, monitoring, leading, and supporting teachers. This report focuses specifically on policies in the area of teachers.